PIV measurements in the draft tube of a down-scale propeller turbine: uncertainty analysis. Issue 1 (1st September 2022) - Sotoudeh, Nahale; Shiraghaee, Shahab; Andersson, Robin; Sundstrom, Joel; Raisee, Mehrdad; Cervantes, Michel
Abstract: In this study, the flow in the conical section of the draft tube of a propeller turbine has been investigated at the best efficiency point and part-load operating conditions using 2D and stereoscopic 3D particle image velocimetry. Since the flow in the turbine is periodic, it is necessary to study the mean flow field rather than the instantaneous one to identify the flow characteristics from a statistical standpoint. However, the statistical convergence of the obtained mean velocity is questionable. Thus, the current work proposes a methodology for investigating the convergence of mean velocity profiles based on the central limit theorem. The methodology is applied to the best efficiency point and part-load results. The results show that 3D PIV results have lower uncertainty than 2D PIV results because measuring the tangential velocity component affects uncertainty, only measured in 3D PIV. The uncertainty difference is more significant, especially in part-load operation, due to the presence of the rotating vortex rope, and therefore a more accurate measurement is necessary to produce a reliable mean flow field. Furthermore, the convergence of the mean velocity profile is faster, with lower uncertainty for best efficiency point results since, at the part-load condition, the tangential velocity component of the flow is higher. In addition, the converged mean velocity profiles show a backflow region with minor rotation in the center, surrounded by a high rotational axial flow during the part-load operation of the turbine.